Низкотемпературная дегидратация цинк-манган(II) фосфатов тетрагидратов - Антрапцева, Надежда Михайловна; Била, Галина Николаевна; Турко, Ольга Васильевна (My University, 2015)
Исследовано поведение при нагревании тетрагидратов фосфатов цинк-марганец (II) общей формулы Zn3-xMnx(PO4)2•4H2O (0<x≤1,00). Было обнаружено, что их термическая стабильность коррелирует с энергетическим состоянием молекул воды и имеет максимум в фосфате с составом Zn2Mn(PO4)2•4Н2O. Исследованы продукты частичного и полного обезвоживания Zn3-xMnx(PO4)2•4H2O. Определены температурные интервалы их образования и термическая стабильность. Воздействие на них скорости нагрева и природы катиона. Приводятся последовательные преобразования тепловой твердой фазы, сопровождающие дегидратацию Zn3-xMnx(PO4)2•4H2O. Behavior at heating of zinc-manganese(II) phosphates tetrahydrates of general formulaZn3 xMnx(PO4)2•4H2O (0<x≤1.00) are investigated. It was found that their thermal stability correlate with theenergy state of water molecules and has maximum in the phosphate with composition Zn2Mn(PO4)2•4Н2O. Products of partial and complete dehydration of Zn3-xMnx(PO4)2•4H2O are investigated. The temperatureintervals of their education and thermal stability are determinated. Influence on them of heating speed andnature of cation is rotined. Sequence of thermal solidphase transformations, that accompany ofZn3-xMnx(PO4)2•4H2O dehydration are adduced.
Keywords: кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; фосфаты цинкмарганца (ІІ); условия обезвоживания; термическая стабильность; phosphates of zinc-manganese(ІІ); dehydration conditions; thermal stability